Formulating the performance improvement strategy for Indonesian higher education in the digital era - Purnamasari, Linda Mauliani; Gaffar, Vanessa; Wibowo, Lili Adi; Dirgantari , Puspo Dewi (Indonesian Research Journal in Education |IRJE|, 2026)
This study aims to formulate a performance improvement strategy for Indonesian higher education institutions in the digital era. A qualitative approach, using in-depth interviews with 10 purposively selected higher education management experts, was employed. Participants were chosen based on their expertise and experience in autonomous public universities. Data were collected over 81 days via online interviews and analyzed using six-stage thematic analysis. The findings identify three strategic stages. First, institutions should develop digital capability (DC) and organizational agility (OA) as foundational capacities. Second, DC and OA act as key enablers of the digital transformation strategy (DTS). Third, DTS can be strengthened by focusing on electronic customer relationship management (E-CRM) to deliver data-driven, personalized services. This study proposes a structured framework for digital transformation in higher education. However, the findings are limited to expert perspectives and require further validation through broader, longitudinal studies.